LITERATURE REVIEW: KOMPONEN NYERI NEUROPATIK PADA NYERI PUNGGUNG BAWAH - Nasywa Maharani Yudiantara; Pagan Pambudi; Ahmad Husairi; Muhammad Welly Dafif; Dona Marisa (Homeostasis, 2022)
Low back pain is a very common health problem and can affect the quality of life. Pain that arises in low back pain can be either nociceptive pain or neuropathic pain. This literature review discusses the neuropathic pain component of low back pain. This review uses a narrative review method. The articles were obtained from keyword searches in the Science Direct, PubMed, and ProQuest databases with a publication range of 2011-2021 in Indonesian or English, and research on the components of neuropathic pain in low back pain. Of the eight articles included in this literature review, the prevalence of neuropathic pain in low back pain was 2.8% - 65.3%. Neuropathic pain can be ruled out using LANSS, DN4, and PDQ. Low back pain with neuropathic pain had symptoms of burning (34.58% - 82.9%), pinpricks (31.77% - 78%), tingling (32.71% - 84.8%), numbness (42.05% - 97%), electric shock (38.97% - 78%), itching (16.82% - 42.4%), cold sensation (12.15% - 48.5%), allodynia (19.62% - 85.4%), 61% hyperalgesia, 14.6% autonomic dysfunction, 100% had dysesthesia, and 100% experienced a decrease in tenderness/prickling. Radicular low back pain is often caused by L5 or S1 root compression and rarely L4. Neuropathic low back pain can be based on an assessment of the symptom profile. Associated risk factors are older age, being a female, greater anthropometric status, the habit of drinking alcohol, smoking, and history of previous lumbar, abdominal or pelvic surgery